The exploration of students' learning gain following immersive simulation – the impact of feedback. Issue 1 (1st January 2019) - Morley, D; Bettles, S; Derham, C
ABSTRACT: With an increasing emphasis on the importance of real-world learning in higher education, coupled with demand for placement experience, simulation has become an increasingly popular pedagogy. However, literature is scant on how students feedforward their learning from the simulation debrief into placement. A mixed-method study of 108 student nurses explored how feedback from the debriefing contributed to students' learning from immersive simulation and whether students used this learning in the placement that followed. In this case, authenticity, realism and interaction were achieved through the use of actors, high fidelity mannequins, clinicians, medical equipment and replicated clinical environments. Results indicated barriers to feedforward at the two stages of the simulation feedback process and the transition of learning into practice. Recommendations identify measures to strengthen the formative feedback phases between the university and practice settings and further enhance the potential of simulation pedagogy.